Catalytic upgrading of sugarcane bagasse pyrolysis vapours over rare earth metal (Ce) loaded HZSM-5: eﬀect of catalyst to biomass ratio on the organic compounds in pyrolysis oil - Vekes, Balasundram; Ruzinah, Isha; Norazana, Ibrahim; Rafiziana, Md. Kasmani; Mohd Kamaruddin, Abd Hamid; Hasrinah, Hasbullah; Roshafima, Rasit Ali (Elsevier, 2018)
The main objective of the current work is to investigate the inﬂuence of catalyst to biomass ratio (by weight%) on the catalytic upgrading of sugarcane bagasse derived pyrolysis vapours over cerium (Ce) loaded Hydrogen exchanged Zeolite Socony Mobil-5 (HZSM-5) catalyst via in-situ ﬁxed bed reactor. The temperature of pyrolysis was kept at 500°C for all investigated samples. The HZSM-5 catalyst was used as a support with 1wt% of Ce as promoter loaded via incipient wetness impregnation method. The biomass sample was ﬁxed at 2g, while the catalyst mass loading was loaded according to the catalyst to biomass ratio which are 0.5:1.0, 1.0:1.0, 1.5:1.0, and 2.0:1.0. For comparison, the non-catalytic and biomass catalytic over HZSM-5 catalyst was also pyrolyzed at the same operating conditions. The results show that the yields of pyrolysis oil and coke were signiﬁcantly inﬂuenced by the use of Ce/HZSM-5 catalyst at various catalyst to biomass ratio than the catalytic pyrolysis over HZSM-5, in which generate higher pyrolysis oil yield (58.0–68.0wt%) and lower coke yield (2.9–4.1%). The increasing loading of mass in Ce/HZSM-5 catalyst has additional eﬀect with respect to C6–C8 hydrocarbon contents in pyrolysis oil than the catalytic samples over the HZSM-5 catalyst. Among the tested catalyst to biomass ratio, the catalyst to biomass ratio of 1.5:1 has demonstrated to be the potential candidates in the catalytic upgrading of sugarcane bagasse derived oxygenated pyrolysis vapours into higher content of C6–C8 hydrocarbons (2.45%) in pyrolysis oil with lower coke yield (3.2%) over Ce/HZSM-5 catalyst. The bi-functional Ce/HZSM-5 catalyst was more eﬀective in suppressing the coke formation in comparison to HZSM-5 catalyst at all investigated catalyst to biomass ratios and this was attributed to the synergistic eﬀect of Ce on HZSM-5 support.